Familial distal trisomy 8(q24.13----qter). - Romain, D R (1989)
Trisomy for the distal part of the long arm of chromosome 8(q24.13----qter) is described in three sibs. The anomaly arose as an adjacent 1 meiotic segregation from a balanced reciprocal translocation t(1;8)(q44; q24.13)mat.